Real-time autodetachment dynamics of vibrational feshbach resonances in multipole-bound states - Kang, Do Hyung (2020)
We investigated vibrational Feshbach resonances of multipole-bound states in the time-domain for the first time. State-specific autodetachment rate measurement in phenoxide (PhO-) dipole-bound state (DBS) [1,2] and 4-cyanophenoxide (4-CP-) quadrupole-bound state (QBS) [3] was performed in the cryogenically-cooled ion trap combined with the time-resolved photoelectron velocity map imaging technique. For the phenoxide DBS, the most prominent 11′1 (+519 cm−1) peak showed τ ~ 33.5 ps. The lifetime of the each vibrational peak is highly mode-dependent to give ~5 ps for the 18′1 (+632 cm−1), and the multi-quanta excitation of the ν11 mode gives ~ 11.9 ps for the 11′2 (+1036 cm−1) and ~9.2 ps for the 11′3 (+1556 cm−1). These mode-specific autodetachment rates are well-described by the Fermi’s golden rule. Interestingly, the 11′118′1 combination mode showed bifurcation dynamics to the 110181 and 111180 neutral product with much faster autodetachment rate of τ ~ 1.4 ps. This result implies that the each bifurcated channel showed accelerated autodetachment dynamics compared to the detachment from the single-mode respectively.